Does speed kill or make friction better?—Designing materials for high velocity sliding. (December 2022) - Eder, S.J.; Grützmacher, P.G.; Rodríguez Ripoll, M.; Gachot, C.; Dini, D.
Highlights: Fully atomistic microstructure modeling for high-speed friction processes. Identification of velocity dependent sliding regimes in fcc alloys Classic plasticity up to sliding speeds of 1% speed of sound. Fluid-like bulk response when sliding at 5–25% speed of sound. When sliding above 25% speed of sound: local melting and shear (re-)localization. Graphical abstract: Abstract: Many modern applications rely on the safe operation of components sliding at high speeds, e.g., in the fields of e-mobility, high-speed manufacturing, or impact-resistant materials. While the impact of mechanical energy and heat on the friction and wear behavior of dry metallic interfaces has been the focus of extensive research in the past, the effect of extreme speeds on the near-surface deformation mechanisms in polycrystalline metals has remained poorly understood. In this work, we have tackled this crucial issue by exploring sliding velocities ranging from 10 to 2560 m/s via large-scale molecular dynamics simulations to identify three distinct deformation regimes in CuNi alloys. The microstructural response does not vary much for any of the considered systems up to sliding velocities of 40 m/s, but then evolves drastically up to a maximum value located between 320 and 1280 m/s depending on the composition. We observe that the degree of plastic deformation at the highest sliding speeds drops down to a level almost as low as for the lowest sliding speeds. We attribute this behavior to a sharp increase in the contact temperature at these high sliding speeds, approaching or even exceeding the bulk melting temperature, which goes hand in hand with a decline in the contact area and the resistance to sliding. Our characterization of the non-linear and non-monotonic material response to increasing sliding velocities will aid the systematic selection of materials and the design of robust components for a variety of high-speed sliding and wear applications.